Demystifying the challenges of low-income housing delivery in urban India: The case of Delhi - Ismail Haque; Malay Kotal; Meera ML (Indian Council for Research on International Economic Relations (ICRIER), 2022)
Increased urbanisation poses serious challenges to adequate housing in the cities of the Global South. Many have focused on the issues of access to serviced land, housing finance, and public subsidy in augmenting the supply of low-income affordable housing while ignoring the criticality of timely allotment and delivery of possession of houses to intended beneficiaries. Drawing on the data from a mixed method study, this article examined the intricacies of lowincome housing delivery in Delhi. The results show that access to completed low-income public housing is primarily constrained due to a prolonged time gap between approval of the allotment letter and delivery of possession to eligible residents, marked by beneficiaries' decades-long struggle, agony, and unending waiting. Pendency in the allotment process has been the greatest impediment to the delivery of possession, contributing to a higher incidence of vacancy in public housing stock across Delhi. There have been several institutional factors (e.g., ownership status of the land, multiple rounds of the survey without tangible outcomes, centre-state conflict over taking the credit of allotments, and the excuse of the Covid-19 pandemic) contributing to the overall delay in allotment and denying the rights of Delhi's lowincome residents to get possession of houses. This has indeed made the housing crisis an institutional crisis or 'crisis within a crisis' in Delhi.
Keywords: R21; R38; R00; 330; Housing crisis; Vacant public housing; Rehabilitation; Delivery of possession; Institutional impediments; Delayed allotments